Smartphones and Educational Apps Use Among Medical Students of a Smart University Campus - Singh, K.; Sarkar, S.; Gaur, U.; Gupta, S.; Adams, O. P.; Sa, B.; Majumder, M. A. A. (Frontiers in Communication, 2021)
Background: Smartphones and medical education Apps are popular with and are widely used by medical students to facilitate peer interactions, communication and collaboration in addition to their “learn anywhere” advantage. Smartphone use by medical students has not been studied in the English-speaking Caribbean. Study objectives were to assess in preclinical students attending the University of the West Indies in Barbados, smartphone ownership, usage and attitudes toward use in medical education. Methods: First and second year preclinical medical students completed a self-administered paper-based questionnaire during the 2018-2019 academic year. Survey questions included sections on smartphone ownership, medical Apps used, phone usage for education related tasks, and the perception on the usefulness of smartphones in medical education. Results: Of 112 participants (response rate 67.4%), 43% considered using the smartphone for medical education when acquiring it but 92% were currently using it for this purpose, with 80.3% (P<0.01) specifically using it for learning anatomy. The majority of the students felt that the use of smartphones would improve their educational experiences (89.1%) (P<0.01), be beneficial to medical faculty for teaching (84.8%) (P<0.01), and could be more effectively used in medical education (50.9%) (P<0.01). For information resources students used Medscape (67.9%) and Mayo Clinic (57.1%) and the most frequently used search engine was Google (95.5%). Most students (67.9%) used medical Apps and 79.5% would buy more useful Apps provided they were affordable. The popular Apps were: ‘Teach me Anatomy’ (11.9%), ‘UpToDate’ (10.3%) and ‘Medscape’ (8.8%). Most students (66.1%) felt a Smart Campus should ensure e-learning platforms were compatible with smartphones and university policies regarding smartphone usage for academic purposes were needed. Conclusion: Findings show that smartphones and related medical education Apps are widely used by medical students and improve their educational experiences. Universities should develop a policy regarding smartphone usage for academic purposes.